Co-infection of Phlebotomus papatasi (Diptera: Psychodidae) gut bacteria with Leishmania major exacerbates the pathological responses of BALB/c mice - Amni, Fariba; Maleki-Ravasan, Naseh; Nateghi-Rostami, Mahmoud; Hadighi, Ramtin; Karimian, Fateh; Meamar, Ahmad Reza; Badirzadeh, Alireza; Parvizi, Parviz (Frontiers in Cellular and Infection Microbiology, 2023)
Clinical features and severity of the leishmaniasis is extremely intricate and depend on several factors, especially sand fly-derived products. Bacteria in the sand fly's gut are a perpetual companion of Leishmania parasites. However, consequences of the concomitance of these bacteria and Leishmania parasite outside the midgut environment have not been investigated in the infection process. Herein, a needle infection model was designed to mimic transmission by sand flies, to examine differences in the onset and progression of L. major infection initiated by inoculation with "low" or "high" doses of Enterobacter cloacae and Bacillus subtilis bacteria. The results showed an alteration in the local expression of pro- and anti-inflammatory cytokines in mice receiving different inoculations of bacteria. Simultaneous injection of two bacteria with Leishmania parasites in the low-dose group caused greater thickness of ear pinna and enhanced tissue chronic inflammatory cells, as well as resulted in multifold increase in the expression of IL-4 and IL-1β and a decrease in the iNOS expression, without changing the L. major burden. Despite advances in scientific breakthroughs, scant survey has investigated the interaction between micro and macro levels of organization of leishmaniasis that ranges from the cellular to macro ecosystem levels, giving rise to the spread and persistence of the disease in a region. Our findings provide new insight into using the potential of the vector-derived microbiota in modulating the vertebrate immune system for the benefit of the host or recommend the use of appropriate antibiotics along with antileishmanial medicines.